2012
DOI: 10.1159/000334980
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Risk of Preclinical Coronary Artery Disease Detected Using Multichannel Cardiac Computed Tomography in Patients with Ischemic Stroke

Abstract: Background: Atherosclerosis is a systemic disease. Many ischemic stroke patients may have concomitant coronary artery disease (CAD). Detection and treatment of preclinical CAD in stroke patients may improve long-term outcome and survival because CAD is a major cause of death during follow-up in stroke patients. However, association between coronary and cerebral artery atherosclerosis in stroke patients has not fully been investigated. This study aimed at examining the frequency and high-risk groups of CAD in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 60 publications
(40 reference statements)
2
59
2
4
Order By: Relevance
“…Also, Sunman et al [21] indicated that age, male gender, dyslipidaemia, and especially family history of premature CAD were associated with severity and extent of non-calcified coronary atherosclerotic plaques as shown by multidetector computed tomographic coronary angiography. Additionally, in a recent study, investigators suggested that a substantial portion of stroke patients had preclinical CAD and there was a clear association between coronary and cerebral artery atherosclerosis in terms of location and burden [22]. The risk of CAD was particularly high in stroke patients with multiple risk factors and atherosclerosis of the carotid and/or vertebrobasilar arteries [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Sunman et al [21] indicated that age, male gender, dyslipidaemia, and especially family history of premature CAD were associated with severity and extent of non-calcified coronary atherosclerotic plaques as shown by multidetector computed tomographic coronary angiography. Additionally, in a recent study, investigators suggested that a substantial portion of stroke patients had preclinical CAD and there was a clear association between coronary and cerebral artery atherosclerosis in terms of location and burden [22]. The risk of CAD was particularly high in stroke patients with multiple risk factors and atherosclerosis of the carotid and/or vertebrobasilar arteries [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study, we used data of women between 55 and 75 years old and of men between 45 and 75 years old. 6,10 Cervicocephalic atherosclerosis and coronary artery stenosis were categorized using the same criteria as those used in the derivation cohort.…”
Section: Validation Cohortmentioning
confidence: 99%
“…The prevalence of severe (≥50% reduction in diameter) occult coronary artery stenosis has been reported to be between 18% and 38% in patients with stroke or TIA and no previous history of CHD. [4][5][6][7] We recently showed that in these patients traditional vascular risk factors, assessed individually or through the Framingham Risk Score (FRS), and the severity of cervicocephalic atherosclerosis are strongly and independently associated with severe coronary artery stenosis detected by 64-section CT. 4 These associations have been confirmed in other studies. [4][5][6] The aim of this study was to derive and validate a simple prediction score for severe occult coronary artery stenosis in stroke/ TIA patients.…”
mentioning
confidence: 99%
“…Patients were indicated for heart CT when they had at least one of the following: (1) presence of atherosclerosis in the intracranial or extracranial cerebral artery; (2) presence of ≥2 risk factors for coronary artery disease such as hypertension, diabetes mellitus, dyslipidemia, cigarette smoking, and central obesity; and (3) old age (males older than 45 years, females older than 55 years). 16 Among the consecutive patients who had been registered in the prospective stroke registry, those with transient ischemic attack were excluded. When a patient was admitted more than twice because of recurrent strokes, only data for the first admission were used for this study.…”
mentioning
confidence: 99%